Constitutional Reconstruction of Legal Protection and Social Welfare Based on Human Security from the Perspective of Substantive Justice - Muhammad Firdiansyah; St. Laksanto Utomo; Amalia Syauket (KRTHA BHAYANGKARA, 2026)
The purpose of this study is to determine the normative construction of legal protection and social welfare in the current constitution, as well as the extent to which it reflects the principles of human security and substantive justice, and the ideal constitutional reconstruction in guaranteeing legal protection and social welfare based on human security to realize substantive justice. The research method used is normative juridical legal research. The results of the study indicate that the constitutional construction of legal protection and social welfare has implicitly reflected the principles of human security and substantive justice, but is still normative and has not been effective in its implementation. Ideal constitutional reconstruction requires strengthening norms that explicitly integrate the principle of human security, affirming the state's obligation to guarantee social welfare as a claimable right, and siding with vulnerable groups, in order to realize substantive justice effectively. It is necessary to carry out a constitutional reconstruction that emphasizes the integration of the principle of human security, strengthening the state's obligation to fulfill social welfare as a claimable right, and ensuring siding with vulnerable groups in order to realize substantive justice effectively.